The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Coupling relationship of industrial structure and coastal utilization in stage-specific development of urban bay: a case study of Xiamen, China (1958–2020) - Weida Lin; Fangfang Shu; Fusheng Luo; Yunpeng Lin; Yuting Lin; Zhijie Chen; Yunhai Li (Frontiers in Marine Science, 2026)
Introduction Coastal zones in bay cities are characterized by high population density, concentrated economic activities, and integrated socio-ecological systems. The dynamic interaction between industrial structural evolution and coastal development in such areas exerts profound impacts on both regional economic growth and ecological sustainability, making it critical to clarify their correlation. Methods By integrating historical marine maps (1958–2020) and remote sensing images (1986–2020) of Xiamen Bay, we extracted the coastline length and utilization data of Xiamen (a typical bay city). Artificial coastlines were categorized into four types based on their functional attributes. The Spearman rank correlation coefficient was then applied to analyze the relationships between coastline length, utilization type, and urbanization indicators, linking these variables to the structure of the primary, secondary, and tertiary industries. Results and Discussion The results indicate that: 1) From 1958 to 2020, the natural coastline length of Xiamen Bay decreased by 283.57 km, accompanied by continuous expansion of artificial coastlines. Specifically, First-type artificial coastline increased by 152.73 km (1958–2002) but decreased by 134.48 km (2002–2020); Second and third type coastlines expanded by 117.07 km and 154.61 km respectively; Fourth-type coastline emerged after 2002 and reached 23.23 km in 2020. 2) At the regional scale, First-type coastline expansion showed a phased positive correlation with the primary industry; Second and third type coastline development was positively correlated with the secondary and tertiary industries (but negatively correlated with the primary industry). 3) The evolution of Xiamen’s coastal zone has shifted from a single economic benefit orientation to a synergistic “economic–ecological–social” model, corresponding to four stages: agricultural reclamation-dominated, initial export-oriented economy, bay-type city construction, and high-quality development transition. Notably, this shift is closely tied to industrial structure adjustments, providing a reference for bay cities to balance economic growth and coastal ecological protection.

A novel ultra-sensitive semiconductor SERS substrate V5S4 nanopompons for the specific detection of antibiotics with AI technology - Weida Zhang; Yusi Peng; Chenglong Lin; Meimei Xu; Shuai Zhao; Dan Li; Yingchun Yang; Yong Yang (Chemical Engineering Journal, 2024)

Optimization of degradation conditions for sulfachlorpyridazine by Bacillus sp. DLY-11 and analysis of biodegradation mechanisms - Xiaojun Lin; Jun Zhang; Zifeng Luo; Jingtong Li; Xue Xiao; Xiujuan Wang; Qianyi Cai; Weida Yu; Junshi Tao; Jingwen Zeng; Hongxing Tu; Jinrong Qiu (Journal of Hazardous Materials, 2024)

MDGA2 Constrains Glutamatergic Inputs Selectively onto CA1 Pyramidal Neurons to Optimize Neural Circuits for Plasticity, Memory, and Social Behavior - Xuehui Wang; Donghui Lin; Jie Jiang; Yuhua Liu; Xinyan Dong; Jianchen Fan; Lifen Gong; Weida Shen; Linghui Zeng; Tonghui Xu; Kewen Jiang; Steven A. Connor; et al. (Neuroscience Bulletin, 2024)

Variable p53/Nrf2 crosstalk contributes to triptolide-induced hepatotoxic process - Zhenyan Hou; Miao Yan; Huixiang Li; Weida Wang; Shen You; Mingjin Wang; Tingting Du; Hui Gong; Wenqun Li; Lin Guo; Shanshan Wei; Bikui Zhang; et al. (Toxicology Letters, 2023)

Decentralized fault-tolerant recovery control of multiple unmanned underwater vehicles on heterogeneous networks - Weida Tian; Wei Zhang; Xue Du; Jia Zeng; Xiaogong Lin (Ocean Engineering, 2023)

Transgenic expression of an insect diapause-specific peptide (DSP) in Arabidopsis resists phytopathogenic fungal attacks - Tingquan Wu; Yongfang Chen; Weida Chen; Shenghao Zou; Yongqing Zhang; Yu’e Lin; Zhaojun Liang; Dingzhong Tang (European Journal of Plant Pathology, 2013)

Genotyping of Trichophyton rubrum by analysis of ribosomal-DNA intergenic spacer regions - Guoling Yang; Lijia An; Qiao Li; Jingrong Lin; Weida Liu; Liji Jin; Xiran Lin (Mycopathologia, 2007)

Integrity of local ecosystems and storm water management in residential areas - Lin Wang; Weida Wang; Zhaoguo Gong (Journal of Ocean University of China, 2006)